Chemical reaction behavior in liquid-liquid system under non-contact microwave irradiation - Asakuma, Y.; Takahashi, S.; Maeda, Y.; Araki, N.; Saptoro, Agus (The Japan Petroleum Institute, 2018)
Â© 2018 Office of the Federal Register. All rights reserved. A Belousov-Zhabotinsky reaction in a liquid-liquid system was observed under non-stirring conditions to evaluate control of the non-equilibrium reaction by microwave irradiation through color changes of the solution. Irradiation power and time, and droplet size were important factors to control the oscillatory reaction in the droplet. During irradiation, the oscillatory period of any droplet sizes became shorter because the reaction rate became faster. In smaller droplets (2 mm), this behavior can be explained by the non-thermal effect because the temperature was equal to the temperature of the surrounding oil. Moreover, the oscillatory behaviors of the reaction in smaller droplets did not change after the irradiation even under higher power and longer irradiation time. On the other hand, shorter oscillatory period was observed in larger droplets (7 mm) after the irradiation, and the special microwave effect persisted. Overall, microwave irradiation was useful for controlling the non-linear reaction in a liquid-liquid system because of activation of the interface through the oil phase.